Social vulnerability is associated with advanced breast cancer presentation and all-cause mortality: a retrospective cohort study - Kayla A. Councell; Ann M. Polcari; Rachel Nordgren; Ted A. Skolarus; Andrew J. Benjamin; Sarah P. Shubeck (Breast Cancer Research)
Abstract Background Disparities in breast cancer mortality persist despite improvements in screening and therapeutic options. Understanding the impact of social determinants of health on disparate breast cancer outcomes is challenging due to heterogeneity of prior assessments. We examined the association between social vulnerability and breast cancer stage at diagnosis and mortality using a standardized measure of population risk for external stressors on health. Methods Using institutional cancer registry data, female patients aged 18 or older diagnosed with breast cancer between 2012 and 2019 were assigned a 2018 Social Vulnerability Index (SVI) rank based upon home address census tract. We used multinomial logistic regression and Cox proportional hazards model to examine the relationships between SVI and breast cancer stage at diagnosis and all-cause mortality. Covariates included age and, when assessing mortality, cancer stage, comorbidities, body mass index, insurance type, and treatment regimen. Results A total of 3,499 women with a median age of 59 (IQR 48–69) were included. 60% were White and 31% were Black. Median SVI was 0.36 (IQR 0.14–0.68) and median follow-up was 58 months (IQR 37.3–83.9). On adjusted analyses, each decile increase in SVI resulted in an 11% (OR 1.11, 95% CI 1.06–1.16, p < .001) and 15% (OR 1.15, 95% CI 1.09–1.21, p < .001) greater odds of presenting with Stage III or IV breast cancer, respectively, compared to DCIS. For patients who underwent surgery (N = 2916), each decile increase in SVI was associated with a 6% increase in all-cause mortality risk (HR 1.06, 95% CI 1.01–1.12, p = .01). Mortality risk was 1.5 times (HR 1.52, 95% CI 1.02–2.26, p = .04) greater for those in the most vulnerable quartile compared to the least vulnerable quartile. Conclusions Women living in socially vulnerable communities presented with more advanced breast cancers and suffered worse survival. The SVI can be used to identify patients at risk for delayed cancer presentation and increased mortality. This tool can inform geographically targeted resource allocation and interventions aimed at reducing breast cancer care disparities.